Pengaruh Kebiasaan Belajar Dan Kreativitas Belajar Siswa Terhadap Hasil Belajar Matematika (Survey Pada SMA Di Kecamatan Ciledug Tangerang) - Nurdeni Nurdeni; Hawa Liberna (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2012)
The objective of this research is to investigate the influence of students learning activity and creativity toward the math learning achievement. In addition it is to know simultaneously the influence of students learning activity and creativity toward the math learning achievement. The research method is used in this research is survey. There are 60 students come from tenth grader of SMA Numaniyah and SMA Fatahillah Ciledug Tangerang as sample of the research, interview, questionner, and achievement test are used to collect the data. The descriptive statistical is used to analyze the data beside person double correlation coefficient, determination coefficient and regression analysis T and F test are used to incate the statistical test. The research was conducted on March 2012. The result of the research show that there is simultaneous influence between students learning activity and creativity toward the math learning achievement of tenth grader students at SMA Ciledug Tangerang. It is stated by the quality regression of Y = -6,227 + 0,85 + 0,683. It indicates that one level of improvement of learning activity and creativity will be followed by the students achievement of -6,227. The students learning activity and creativity variables indicates the significance influence toward the students learning achievement. It is shownby the determination coefficient of R2 = 0,777 and F test score = 99,459.